Trends in Practicum Tool Development with PjBL to Improve Digital Literacy, Process Skills, and Learning Outcomes: A Systematic Review - Fahmi Firdaus; Susilawati Susilawati; Ahmad Harjono (Current Educational Review, 2025)
In the context of the rapidly evolving digital era, educational systems worldwide are facing significant challenges in fostering digital literacy, enhancing scientific process skills, and improving overall learning outcomes among students. This article presents a systematic review of the trends in the development of practicum tools utilizing the Project-Based Learning (PjBL) model from 2015 to 2024. The review aims to identify research patterns and provide insights into how these innovative tools can contribute to digital literacy and science process skills. Through the analysis of 1,000 documents indexed by Google Scholar, it is found that research interest surged notably between 2020 and 2023, reflecting a growing emphasis on integrating technology into education. The findings indicate that practicum tools developed under the PjBL model have effectively enhanced students' engagement with scientific concepts and real-world applications. Moreover, the review highlights the predominant types of publications in this field and the most frequently cited sources, shedding light on significant contributions to the ongoing discourse in science education. This research underscores the need for continued exploration and development of technology-based practicum tools to equip students with essential skills for the future